Diseño de un plan de marketing para la comercialización y distribución de truchas en la ciudad de Latacunga, provincia de Cotopaxi - Arias Pila, Adriana Veronica (2015)
The objective of this project aims to contribute to the positioning of the business of trout in the Pachosalag sector in the Ltacunga’s markets, in addition to improving their level of sales by developing a marketing plan, which will reflect result favorable to business .The main problem is the low position that has trout in the field business in the markets of the Latacunga city, which originated at the lack of implementation of marketing tools: such as advertising, pricing, selection of distribution channels that allow to publicize its product (trout), fulfilling the expectations of customers….